Growth performance and hematological changes of weaned beef calves diagnosed with respiratory disease using respiratory scoring and thoracic ultrasonography - Cuevas-Gómez, Inmaculada (J Anim Sci, 2020)
This study investigated 1) the effect of clinical bovine respiratory disease (BRD) and associated lung consolidations on growth performance and hematological profiles of recently weaned beef calves and 2) the relationship between clinical respiratory signs and lung consolidation detected by thoracic ultrasonography (TUS). One hundred and fifty-three weaned beef calves (209 days old [SD: 35.8] and 306 kg [SD: 26.3], at arrival) purchased and transported from auction markets were accommodated indoors in concrete slatted floor pens. Calves were weighed weekly from arrival until day 28 and on day 65 post-arrival. Assessment of BRD and blood sample collection for hematological profiles were performed on scheduled days (at arrival, on days 7, 14, and 28) and on other days upon BRD diagnosis. Animals were assessed for BRD using a total clinical respiratory score (CRS) of five clinical signs (rectal temperature, ear position, cough, nasal secretion, and eye secretion with each ranging from normal [0] to abnormal [3]) and TUS scores (normal [0] to lung consolidation ≥ 1 cm(2) [2]). Based on CRS, 35% of calves were CRS+ (CRS ≥ 5) and 65% were CRS− (CRS < 5). Although no lung consolidations (TUS−) were detected at arrival, 34% of calves developed lung consolidation (≥1 cm(2)) (TUS+) during the first 28 d post-arrival. Only fever (>39.6 °C) and nasal discharge were weakly associated (r = 0.19, P <0.05) with lung consolidation. On the day of BRD detection, neutrophil number and neutrophil:lymphocyte ratio were 58% and 73% greater, respectively, in BRD calves with lung consolidation compared with healthy calves. From day 0 to 65, calf average daily gain (ADG) did not differ (P >0.05) between CRS+ and CRS− calves but was 0.09 kg/d lower (P < 0.05) for TUS+ compared with TUS− calves. Calves classified as BRD (CRS + TUS ≥ 5) with lung consolidation had lower (P < 0.05) ADG from arrival until day 28 than healthy calves and BRD calves without lung consolidation (0.11 ± 0.10 vs. 0.53 ± 0.07 vs. 0.57 ± 0.10 kg/d, respectively); however, no differences in ADG were observed from day 0 to 65. Conventional methods to diagnose BRD failed to detect calves with lung lesions. TUS is a useful tool to detect lung lesions and its implementation in combination with CRS should provide a more accurate and early diagnosis of BRD, which is fundamental to successful treatment, animal welfare, and growth performance.